2022
DOI: 10.4103/jomfp.jomfp_236_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of XPD and XPG gene polymorphism in oral squamous cell carcinoma and tobacco chewers

Abstract: Introduction: The study indicated that XPD and XPG gene polymorphism is associated with the development of oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma. Xeroderma pigmentosa (XP) is a part of the complex DNA repair system. Xeroderma pigmentosum group G (XPG) and xeroderma pigmentosum group D (XPD) gene function in the nucleotide excision repair (NER) pathway. XPG and/or XPD gene alterations can cause defective DNA repair efficiency which ultimately leads to genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the sensitivity analysis, each individual study included in the meta-analysis was sequentially removed to observe its influence on the pooled ORs. We found that two studies significantly affected the pooled OR value [ 8 , 10 ], suggesting relative instability in the results of this meta-analysis (Fig. 8 for allele model).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In the sensitivity analysis, each individual study included in the meta-analysis was sequentially removed to observe its influence on the pooled ORs. We found that two studies significantly affected the pooled OR value [ 8 , 10 ], suggesting relative instability in the results of this meta-analysis (Fig. 8 for allele model).…”
Section: Resultsmentioning
confidence: 93%
“…A total of one hundred and eighty-two records were identified based on the search strategy, and two additional records were added after screening reference lists. One hundred and thirteen records were screened, and twelve studies were included in this meta-analysis [ 7 , 8 , 10 19 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations